Kualitas Pelayanan Administrasi Akademik di Perguruan Tinggi (Studi pada Fakultas Ilmu Administrasi Universitas Brawijaya) - Anisah, Anisah; Haryono, Bambang Santoso; Mindarti, Lely Indah (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2020)
The purpose of this study is to describe and analyze the objective conditions of academic administrative services, service quality based on service quality indicators, and supporting and inhibiting factors in the academic administration service process at the Faculty of Administrative Sciences, Universitas Brawijaya. The results of this study indicate that the service is in accordance with the Standard Operating Procedure (SOP), standardized, to improve the quality of service, it will conduct training of civil service operators and excellent service training. Based on service quality indicators, it shows that the results are sufficient to provide quality service results. The researcher concludes the policy, and physical and non physical resources support each other to achieve the quality of academic administrative services. Researchers suggest that all forms of academic administrative services are carried out on line and there are Standard Operating Procedures.